2022
DOI: 10.3390/ijerph19137668
|View full text |Cite
|
Sign up to set email alerts
|

Discussions of Flavored ENDS Sales Restrictions: Themes Related to Circumventing Policies on Reddit

Abstract: Objective: To examine conversations among JUUL users on Reddit related to restrictions on flavored ENDS and the shifting policy landscape. Methods: Posts and comments (n = 166,169) between May 2019 and May 2020 on the subreddit r/JUUL were scraped using pushshift.io API. Keyword filters were used to identify texts discussing flavored ENDS products (n = 33,884 texts). These were further narrowed down to texts discussing flavor policy workaround strategies (n = 7429) and N-gram analysis was performed. Finally, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…N-grams connected sequences of n items (words) from a given sample of text or speech (Broder et al, 1997). We examined top unigrams, bigrams, and trigrams and found that the trigrams were the most interpretable for salient content themes, consistent with previous social media tobacco research (Benson et al, 2020; Czaplicki, Kostygina, et al, 2020; Malik et al, 2021; N. Silver et al, 2022).…”
Section: Methodssupporting
confidence: 74%
“…N-grams connected sequences of n items (words) from a given sample of text or speech (Broder et al, 1997). We examined top unigrams, bigrams, and trigrams and found that the trigrams were the most interpretable for salient content themes, consistent with previous social media tobacco research (Benson et al, 2020; Czaplicki, Kostygina, et al, 2020; Malik et al, 2021; N. Silver et al, 2022).…”
Section: Methodssupporting
confidence: 74%
“…We used a search filter previously developed and validated by our team to identify flavoured e-cigarette products (ie, posts referencing flavours of e-cigarettes, other electronic nicotine delivery systems, e-liquids, e-juice, etc). 45 Sample search rules included “flavor OR flavors OR flavored OR flavorant OR flavorants OR flavoring OR flavoring”, etc.…”
Section: Methodsmentioning
confidence: 99%